Histopathological Features of the Lung Parenchyma in a 64-Year-Old Male Patient with Post-COVID-19 Infection with Spontaneous Pneumothorax Dextra Due to AlveolarPleural Fistula (APF): A Case Report - Putu Erika Paskarani; Ni Wayan Winarti; Santi Maya Lestari Siahaan; Made Dalika Nareswari (Indonesian Journal of Cancer, 2022)
Introduction: Histopathological features of the lung parenchyma due to the Alveolar-Pleural Fistula (APF) in a patient with post-COVID-19 infection have not been reported. APF usually occurs after a spontaneous pneumothorax. Spontaneous pneumothorax is an abnormal traumatic accumulation of air within the pleural space. It is classified as primary or secondary pneumothorax based on multiple risk factors.Case Presentation: A sixty-four-year-old patient was referred from one of the remote hospitals in the west of Bali due to spontaneous simple pneumothorax dextra. A week after being diagnosed with COVID-19 infection, the patient underwent a bullectomy procedure and was clinically diagnosed with recurrent spontaneous pneumothorax dextra due to APF. Then, the bullectomy specimen was sent to the anatomical pathology laboratory. Histopathology test revealed extensive areas of necrosis and fibrosis with scattered lymphocytes and emphysematous alveoli found in APF lesions. Conclusions: In conclusion, the evidence of extended fibrosis, which destroys the pulmonary parenchymal septum and dilated alveoli with diffuse fibrosis in the subpleural and intraparenchymal areas, may cause impairment of both perfusion and ventilation. Unfortunately, viral cytopathic like-changes related to COVID-19, such as multinucleated cells with large nuclei, amphophilic cytoplasm, and prominent nucleoli in alveolar spaces with intranuclear inclusions, were not found in this case. In this case, surgery is needed in case of fistula, either related or unrelated to infection of the pleural cavity indicating the patient’s functional recovery.